A study of the teratogenic effect of Ciprofloxacin - Jahangir, Selim Mohammed; Islam, AFM Saiful (Bangladesh Journal of Physiology and Pharmacology, 2009)
Drugs or medicinal agent should only be used in pregnancy if there is proven benefit to the mother and no potential teratogenic risks. Present study was performed to evaluate the teratogenic effect of modern drug, Ciprofloxacin a Fluoroquinolone derivative, which has been introduced in Bangladesh. This was felt necessary because this has been found to be used indiscriminately at all levels of the prescribers and there is no strong evidence to its safety in pregnancy The work described here is to evaluate the teratogenic effect of Ciprofloxacin using swiss albino mice. The pregnant mice were divided into two different groups which received Normal Saline and Ciprofloxacin [25 mg/kg body weight.] given from 6th to 15th day of gestation. Neither the control group nor the experimental group revealed any sign of external deformity and cleft palate. DOI: 10.3329/bjpp.v22i1.3562 Bangladesh J Physiol Pharmacol 2006; 22(1/2) : 9-11